Pengaruh Pengelolaan Hara NPK Terhadap Ketersediaan N Dan Hasil Tanaman Padi Sawah (Oryza Sativa L.) Di Desa Waelo Kecamatan Waeapo Kabupaten Buru - Rudy Soplanit; Siti H Nukuhaly (Agrologia, 2012)
This study was conducted in Waelo Village, Waeapo Subdistrict, Buru District, with the objectives to determine N fertilizer application timing to increase rice yield and to understand the response of two rice varieties commonly grown in Waeapo. The experimental method used in this study was a Randomized Complete Block Design, with several fertilization treatments (NPK, NK,NP, PK and control), and rice varieties (Membramo and Mekongga), and with three replications. The results showed that administration of N fertilizer (NP, NK, NPK) gave significant effects on plant height, leaf color, full grain number per panicle, 1000 grain weight, dry grain yield, soil N content and leaf N content;  meanwhile it did not affect soil reaction (pH). A low rice yield was obtained in the treatment without N fertilizer, with 2.50 kg dry grain yield per plot and PK treatment with 2.78 kg  dry grain yield per plot.